THE ROLE OF SPORT-RELATED NASAL BONE FRACTURE IN DEVELOPMENT OF SLEEP APNOEA IN CHILDREN - Marta Kras; Agata Karasiewicz; Maja Kuklo; Dominik Łepecki; Aleksandra Karolak; Andrzej Wydrych; Ewa Wietrzykowska; Patryk Pindlowski; Piotr Trojan (International Journal of Innovative Technologies in Social Science, 2026)
Sport-related injuries have been reported as one of the top three causes of nasal bone fractures in the paediatric population regardless of the region. The most common sport disciplines responsible for nasal bone fractures are ball games like football, basketball and baseball. The diagnosis of nasal bone fracture is especially difficult in children consequential to a different anatomical structure of their nose than that of an adult’s. Masked by edema etc it is frequent for a paediatric fracture to be omitted on first examination, therefore it is crucial for physicians to take history and examine the young patients very carefully despite the child’s potential non-cooperative spirit. Paediatric nasal fractures are most commonly managed with closed reduction as surgical treatment is often delayed until the nose's development is complete, which occurs around adolescence, in order to avoid interfering with the growth centre. This approach may result in various post-traumatic complications, typically requiring frequent follow-up visits and secondary surgical treatment. As a result, it is critical to pay close attention to the underlying structural nasal structure during the initial diagnosis and treatment to avoid complications such as septal hematoma, septal deviation, and nasal obstruction. This review aims to outline the most frequent and severe long-term complications, stress the significance of early diagnosis and treatment, and provide strategies for preventing nasal bone fractures both re-injury and re-injury in children. Additionally, we would like to explore the likelihood that children will experience post-traumatic nasal obstruction, which can subsequently result in sleep apnea, reduced quality of life, and impaired athletic performance.